Self-examination physiological characteristics of an organism of women who specialize in powerlifting - Gordienko Y. V. (Kharkov National Pedagogical University, 2010)
Physiological features of the female body is one of the main factors that underpin sports training process and the result of competitive athletes. This article examines the impact of regular exercise on the body weightlifting women. The features of physiological status of female athletes and performance of women in connection with the peculiarities of the reproductive function. These and analyzed the results of questioning coaches and athletes, Poltava region, which specialize in powerlifting.